2009
DOI: 10.1080/13697130802585576
|View full text |Cite
|
Sign up to set email alerts
|

Topical estrogen therapy in the management of postmenopausal vaginal atrophy: an up-to-date overview

Abstract: Vaginal atrophy, a manifestation of estrogen deprivation after the menopause, could affect up to 60% of women, with a significant impact on their quality of life. It is often under-diagnosed and inadequately treated. Symptoms are more common and severe in breast cancer survivors. Systemic estrogen replacement therapy may be unacceptable for many women because of the concerns over possible risks and may not cure vaginal symptoms in up to 45% of users. Non-medicated vaginal lubricants or moisturizers have been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 73 publications
0
67
0
10
Order By: Relevance
“…In recent years, the use of locally applied vaginal low-dose estrogen has been advocated in preference to systemic treatment and is considered to be the best therapy for vaginal atrophy (3,12,13). Another broadly discussed question is the possible use of low-dosed vaginal estrogens for the treatment of the symptomatic vaginal atrophy (vaginal dryness, dyspareunia, etc.)…”
Section: Treatment Of Vaginal Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the use of locally applied vaginal low-dose estrogen has been advocated in preference to systemic treatment and is considered to be the best therapy for vaginal atrophy (3,12,13). Another broadly discussed question is the possible use of low-dosed vaginal estrogens for the treatment of the symptomatic vaginal atrophy (vaginal dryness, dyspareunia, etc.)…”
Section: Treatment Of Vaginal Atrophymentioning
confidence: 99%
“…Hence, a mature vaginal epithelium is a prerequisite for establishing and maintaining physiological lactobacillary microflora (11). Vaginal atrophy is associated with reduced efficacy of the barrier function of the vaginal epithelial lining and, as a consequence facilitate the penetration of pathogenic micro-organisms (12,13). Risk factors for disturbing the vaginal ecosystem can be (1) endogenous (variations in hormone levels, contraceptives, menstruation, pregnancy and lactation, diabetes mellitus, systemic diseases) or (2) exogenous.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Baghdadi and Ewies 36 concluded that no studies show evidence of endometrial proliferation after 6 to 24 months of use of topical estrogen, so the literature thus provides reassurance regarding the safety of low-dose vaginal estrogen preparations and does not support the concomitant use of systemic progestins for endometrial protection. This evidence has been endorsed in recent clinical practice guidelines issued by The International Menopause Society 37 and The…”
Section: Local Estrogen Therapymentioning
confidence: 99%
“…Выявлено, что эстрогены улучшают трофику эпите-лия влагалища, уретры, мочевого пузыря; повышают пе-риуретральную васкуляризацию, являющуюся важным фактором регуляции давления закрытия уретры; увеличи-вают максимальное давление закрытия уретры, концен-трацию и чувствительность адренорецепторов [25]. Уста-новлено, что препараты ЗГТ восстанавливают соотноше-ние протеогликана и коллагена до уровня, существовав-шего в перименопаузе.…”
Section: российский вестник акушера-гинеколога 3 2015unclassified